PENGARUH KARAKTERISTIK WIRAUSAHA DAN POTENSI KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA DENGAN KEBIJAKAN PENGEMBANGAN UKM SEBAGAI MODERATING (Studi Pada Pengusaha Kecil di Kota Surakarta dan Sekitarnya) - Suseno, Djoko (Exsplorasi, 2008)
ABSTARCT The success is influenced by characteristics inside of the Entrepreneur, potency of manufacturing that show the power in managing manufacture and the support of UKM developing wisdom by an institution. The objective of this research is to know the influence of entrepreneur characteristics and potency of manufacturing toward the success by UKM developing wisdom and the success of Manufacturing. The analysis id done by structural equation modeling (SEM) which is stuitable with the problem statement and hypothesis. It is a confirmation technique or proving the existing of theory, that have ever been tested and arranged in a model. The result of comparing indicators goodness of indices show that chi square 74,323 of probability 0,402 CMIN 1,032 RMSEA 0,0023 AGFI 0,786 TLI 0,987 and CFI 0,990. The result of modal evaluation shows that all of model research is good. The result of the result prove that entrepreneur characteristic  have positive influences significantly toward the success of manufacture. Potency of manufacturing has no influences significantly to ward the success of manufacture. The other findling is that the UKM developing wisdom doesn’t moderate either the influence of entrepreneur characteristics toward the success of manufacture, or the influence of manufacturing Potency toward the success of manufacture. Key word: entrepreneur characteristics, manufacturing potency,UKMDeveloping Wisdom, success of   manufacture.